COVID-19 with underdiagnosed influenza B and parainfluenza-2 co-infections in Saudi Arabia: Two case reports - Sari T. Alhoufie; Naif H. Alsharif; Khalid O. Alfarouk; Nadier A. Ibrahim; Ali M. Kheyami; Alanoud A. Aljifri (Elsevier, 2021)
The emerging of the COVID-19 pandemic is currently challenging for the public health system globally. Beyond SARS-CoV-2 pathogenicity, co-infections with recycling respiratory pathogens, whether bacterial, viral, or fungal, might increase disease symptoms, morbidity, and mortality.In this study, we reported two COVID-19 cases in the early phase of the virus spread in Saudi Arabia with underdiagnosed respiratory viruses' co-infections, influenza B and Parainfluenza-2, detected retrospectively. Fortunately, both patients recovered and were discharged home.Underestimation of co-infection among COVID19 patients might lead to hospital stay prolongation and increases morbidity and mortality. Therefore, it is crucial to consider and screen for co-infecting pathogens among COVID-19 patients and those with risk factors.